Odpowiedź:
a)
delta = - 4 * 2 * (-4) = 4 + 32 = 36
x0 nr 1 = (2 - )/(2*2) = -4/4 = -1
x0 nr 2 = (2 + )/(2*2) = 8/4 = 2
Tak
b)
delta = - 4 * 1 * 4 = 16 - 16 = 0
x0 = -4/(2*1) = (-2)
Nie
c)
2x(x+6)+x(x+21)-30 = 2x² + 12x + x² + 21x - 30 = 3x² + 33x - 30
delta = - 4 * (-30) * 3 = 1089 + 360 = 1449
Pierwiastek z delty nie jest całkowity, przez co ci na pewno nie wyjdzie liczba całkowita jako miejsce zerowe.
Nie
d)
0,5*(x-2)²+1 = 0,5x² - 2x + 3
delta = - 4 * 0,5 * 3 = 4 - 6 = (-2)
Szczegółowe wyjaśnienie: